UPAYA PENCEGAHAN STUNTING MELALUI PROGRAM GEBYAR PEKAN KESEHATAN DI DESA SENGKATI BARU - Fitri, Adelina; Aswin, Budi; Ningsih, Vinna Rahayu; Putra, Ashar Nuzulul; Rahmat, Andree Aulia; Putri, Fitria Eka; Hubaybah, Hubaybah (Jurnal Salam Sehat Masyarakat (JSSM), 2024)
Stunting is a serious public health problem in many developing countries, including Indonesia. This research aims to evaluate the effectiveness of the "Gebyar Pekan Kesehatan" program to prevent stunting in Sengkati Baru village. The research method used is a communication intervention study, involving the active participation of the local community. Data were collected through pre-questionnaire surveys and anthropometric measurements on children under five. This research shows a significant reduction in stunting rates and an increase in public awareness about balanced nutrition. The "Gebyar Pekan Kesehatan" program has been proven effective in preventing stunting in Sengkati Baru village and has the potential to be adopted in other areas that face.